The effectiveness of a classroom-based phonological awareness program for 4–5-year-olds - Kelly, C.; Leitão, Suze; Smith-Lock, K.; Heritage, B. (Informa Healthcare, 2017)
Purpose: Numerous studies have reported a robust relationship between early phonological awareness (PA) and subsequent reading achievement, in addition to the critical role of the alphabetic principle in predicting and supporting later reading and spelling development. Given this association, there has been an increasing push to teach these skills to young children prior to word level reading and spelling instruction. This study evaluated the effectiveness of the Cracking the Code (CtC) program with students aged 3;8–5;4. CtC is a teacher-implemented program, designed to explicitly target PA skills and alphabet knowledge. Method: A pre-test post-test group design was used to evaluate the effectiveness of the program. Four schools in metropolitan Western Australia were randomly assigned to either the control or experimental condition within a parallel groups design. The control group participated in an alternative program matched for duration and frequency, targeting semantics and grammar. Result: The children in the experimental condition improved significantly more in PA, alphabet knowledge and non-word reading, and spelling after intervention than the control group. Conclusion: These findings demonstrate that classroom-based, teacher-delivered PA and alphabet knowledge instruction can be effective for 3;8–5;4 year-olds.